2022
DOI: 10.1002/hep.32213
|View full text |Cite
|
Sign up to set email alerts
|

Switch‐associated protein 70 protects against nonalcoholic fatty liver disease through suppression of TAK1

Abstract: Background and Aims NAFLD is a progressive disease without known effective drug treatments. Switch‐associated protein 70 (SWAP70) is a guanine nucleotide exchange factor that participates in the regulation of many cellular processes. However, the role of SWAP70 in NAFLD remains unclear. This study aimed to identify the function and mechanism of SWAP70 in NAFLD. Approach and Results The results showed that the expression of SWAP70 was significantly increased in mice and hepatocytes after metabolic stimulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
1
13
1
Order By: Relevance
“…Although how TXNIP regulates TAK1 in LSECs still needs to be further studied, our results show that TXNIP interacts with TAK1, thus attenuating TAK1 phosphorylation and subsequent JNK signaling in LSECs. The potential role of TAK1 in various liver diseases, including ischemia-reperfusion injury, NAFLD, NASH, and HCC, has been well defined (Inokuchi et al , 2010; Qian et al , 2022; Tan et al , 2020; Zhang et al , 2022). Suppression of TAK1 and its downstream signaling significantly promotes liver injury, inflammation, fibrosis, and tumor formation (Inokuchi et al ., 2010; Tan et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although how TXNIP regulates TAK1 in LSECs still needs to be further studied, our results show that TXNIP interacts with TAK1, thus attenuating TAK1 phosphorylation and subsequent JNK signaling in LSECs. The potential role of TAK1 in various liver diseases, including ischemia-reperfusion injury, NAFLD, NASH, and HCC, has been well defined (Inokuchi et al , 2010; Qian et al , 2022; Tan et al , 2020; Zhang et al , 2022). Suppression of TAK1 and its downstream signaling significantly promotes liver injury, inflammation, fibrosis, and tumor formation (Inokuchi et al ., 2010; Tan et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of TAK1 and its downstream signaling significantly promotes liver injury, inflammation, fibrosis, and tumor formation (Inokuchi et al ., 2010; Tan et al ., 2020). TAK1 hyperactivation, on the other hand, induces hepatic steatosis, inflammation, and fibrosis, whereas TAK1 activity suppression alleviates the progression of these diseases (Inokuchi et al ., 2010; Mahata et al , 2021; Qian et al ., 2022; Zhang et al ., 2022). Here, TAK1 inhibition attenuated JNK activation, restored the eNOS level, and down-regulated cytokines and adhesion molecule in Txnip -deficient LSECs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also revealed several CNVR-harbored genes related to the immune system process (SWAP70, FYN, ORAI1, TRPM2, and FOXO3). The SWAP70 gene (CNVR_Chr11:157.8-157.9 Mb), is essential for normal B-cell migration that immobilizes F-actin filaments on phagosomes, contributing to immune regulation such as maturation and differentiation of immune cells [124,125]. Interestingly, Karimi et al [126] reported the SWAP70 gene as a potential candidate gene for response to Aleutian mink disease virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we comprehensively analyzed the transcriptomes, metabolomes, and gut microbiotas in WT mice and CD1d KO mice fed with HFD or NCD. NAFLD is a metabolism-associated chronic disease, which is characterized by both triglyceride and free cholesterol accumulation (Qian et al, 2021). Indeed, dysregulated cholesterol metabolism might contribute to NAFLD progression (Hu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%